Impacts of fish farming on elemental stoichiometry, fluorescence components, and stable isotopes of dissolved organic matter in a tropical reservoir. (1st January 2021) - Chaves, R.C.; Figueredo, C.C.; Boëchat, I.G.; Gücker, B.
Abstract: Aquaculture impacts on aquatic organic matter and ecosystem integrity are poorly understood, especially in tropical regions. Here, we investigated the impacts of Nile tilapia net cage farming on the elemental stoichiometry, fluorescence components, and stable isotopes of dissolved organic matter (DOM) of the large, tropical Furnas Reservoir (SE Brazil). Early-stage fish farming, i.e., relatively small and recently implemented farms, had detectable incipient effects on DOM characteristics, and these effects differed between reservoir branches. In the less eutrophic Rio Grande branch of the reservoir, we found a reduction in natural humic-like DOM components and an increase in a protein-like DOM component as far as 100 m away from fish farms. Further, we observed a decrease in δ 15 N-TDN due to fish farming. In the more eutrophic Rio Sapucaí branch, there were only local decreases in C:N ratios, as well as rises in C:P and N:P of DOM due to fish farming. These results suggest that early-stage fish farming had local but detectable effects on aquatic DOM that depended on previous eutrophication levels and highlight the need to assess the early impacts of fish farming on tropical reservoirs by combining different monitoring strategies. Graphical abstract: Image 1 Highlights: Effects of early-stage fish farming on reservoir DOM were studied. Small effects on DOM characteristics in up to 100 m distance of farms. Decreases in natural humic-like DOM and d15N-TDN, increases in protein-like DOM. Local decreases in C:N, increases in C:P and N:P ratios of DOM. Effects on aquatic DOM depended on background eutrophication levels. Abstract : Fish farming affects DOM elemental stoichiometry, PARAFAC components, and δ 15 N-TDN in a large tropical reservoir.